2014
DOI: 10.1111/bcp.12281
|View full text |Cite
|
Sign up to set email alerts
|

The H3antagonist ABT-288 is tolerated at significantly higher exposures in subjects with schizophrenia than in healthy volunteers

Abstract: AIMSABT-288 is a potent and selective H3 receptor antagonist with procognitive effects in several preclinical models. In previous studies, 3 mg once daily was the maximal tolerated dose in healthy volunteers. This study characterized the safety, tolerability and pharmacokinetics of ABT-288 in stable subjects with schizophrenia. METHODSThis was a randomized, double-blind, placebo-controlled, dose-escalating study of ABT-288 (10 dose levels, from 1 to 60 mg once daily for 14 days) in stable subjects with schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…18 In a phase 1 multiple dose study of subjects with schizophrenia, doses of ABT-288 up to 60 mg once daily were administered and doses up to 45 mg once daily were safe and well tolerated. 19 Frequently reported adverse events such as abnormal dreams, insomnia, headache, and dizziness were similar to those observed in phase 1 studies of healthy volunteers and elderly subjects. 20 Subjects with schizophrenia in the phase 1 study tolerated higher daily doses and plasma exposures of ABT-288 than healthy adults and elderly subjects, where the maximum tolerated dose was 3 mg once daily.…”
Section: G M Haig Et Alsupporting
confidence: 56%
See 3 more Smart Citations
“…18 In a phase 1 multiple dose study of subjects with schizophrenia, doses of ABT-288 up to 60 mg once daily were administered and doses up to 45 mg once daily were safe and well tolerated. 19 Frequently reported adverse events such as abnormal dreams, insomnia, headache, and dizziness were similar to those observed in phase 1 studies of healthy volunteers and elderly subjects. 20 Subjects with schizophrenia in the phase 1 study tolerated higher daily doses and plasma exposures of ABT-288 than healthy adults and elderly subjects, where the maximum tolerated dose was 3 mg once daily.…”
Section: G M Haig Et Alsupporting
confidence: 56%
“…An increase in psychosis-related events were observed in the phase 1 study in subjects with schizophrenia, but the inflection point appeared to occur at doses greater than those used in this study. 19 Higher rates of psychosis were not reported in previous schizophrenia studies with H3 antagonists. 16,17 However, doses in all of these trials were comparable to those used in other populations, not the 10-fold increase administered in this study.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Hence working on this hypothesis two drugs were introduced, such as ABT-288 and GSK239512 (Scheme 4). The phase I and phase II clinical trials of the former one have shown tremendous anti-AD activity while the later drug has not shown any considerable progress in low-moderate AD patients [70][71][72][73].…”
Section: B) Tau Dephosphorylationmentioning
confidence: 99%